INDONESIAN GEOPOLITICS: EXPLORING ROLES ON THE NEW GEOPOLITICAL MAP - Kunkunrat Kunkunrat (Jurnal Multidisiplin Sahombu, 2023)
In the era of globalization and increasingly complex geopolitical dynamics, a deep understanding of a country's geopolitical position is crucial. This research aims to investigate Indonesia's role in the context of a geopolitical map that continues to change and develop. This research uses a qualitative approach with descriptive methods. The research results show Indonesia's crucial role in global geopolitical dynamics, especially facing changes in the "new geopolitical dynamic map." Indonesia, as the largest archipelagic country, carries responsibility as a guardian of regional stability and a contributor to the global order. Maritime disputes, great power competition and global challenges require wise responses, with Indonesia faced with the complex task of maintaining a balance between national interests and global responsibilities. Adaptation capacity is needed through the development of strong diplomacy, cohesive foreign policy and responsive strategies. Indonesia, with its potential as a balancing force, can make a positive contribution to peace and development at the global level, but this challenge requires active involvement and a firm stance from Indonesia in facing the ever-developing geopolitical dynamics.